ANALISIS PENDAPATAN DAN KELAYAKAN USAHA PETANI MINYAK BUAH MERAH DI KAMPUNG MINDERMES KABUPATEN MANOKWARI SELATAN - Ketysia I Tewernusa; Oktopianus Dowansiba; Maria Magdalena Semet (Lensa Ekonomi, 2025)
This study aims to determine the income level and business feasibility of red fruit oil farmers in Mindermes Village, Dataran Isim District, South Manokwari Regency. This type of research is descriptive quantitative research. The population in this study includes all red fruit oil farmers in Mindermes Village, Dataran Isim District, South Manokwari Regency. The sampling technique used is the census method, in which the entire population is used as the sample. The type of data used is primary data, while the method of analysis uses income analysis and the Revenue/Cost (R/C) Ratio formula. The results of the study show that the average income per harvest season for red fruit farmers in Mindermes Village, Dataran Isim District, South Manokwari Regency is IDR 3,263,754. The Revenue/Cost (R/C) ratio is 2.6, which means that the red fruit oil farming business in Mindermes Village is feasible to pursue.